1989
DOI: 10.1007/bf00042250
|View full text |Cite
|
Sign up to set email alerts
|

Vertical profile and canopy organization in a mixed deciduous forest

Abstract: A combination of optical measurements of leaf heights and observations on litterfall provided a vertical and temporal description of the leaf community structure in a tall, Liriodendron forest on the Maryland coastal plain. Leaf area, mass, and number were bimodally distributed with height. Median leaf number occurs far below (7-8 m) and median leaf mass far above (22-23 m) the median leaf area (18-19 m). Tree species exhibited leaf stratification into 3 height levels: understory (0-10 m), mid canopy (10-25 m)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…Average annual precipitation (MAP) in this area is 108 cm and the region is classified as a humid subtropical climate (Kö ppen classification by FAO GeoNetwork). This seasonally deciduous forest is dominated by Liriodendron tulipifera in the upper and mid-canopy, Fagus grandifolia in the lower mid-canopy and Carpinus caroliniana in the understory (Parker et al, 1989;Brown and Parker, 1994). Most foliage is produced during spring leaf flush when the canopy is open (Brown and Parker, 1994), although canopy closure of >99% light attenuation is reached at the height of the summer growing period.…”
Section: Collection Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Average annual precipitation (MAP) in this area is 108 cm and the region is classified as a humid subtropical climate (Kö ppen classification by FAO GeoNetwork). This seasonally deciduous forest is dominated by Liriodendron tulipifera in the upper and mid-canopy, Fagus grandifolia in the lower mid-canopy and Carpinus caroliniana in the understory (Parker et al, 1989;Brown and Parker, 1994). Most foliage is produced during spring leaf flush when the canopy is open (Brown and Parker, 1994), although canopy closure of >99% light attenuation is reached at the height of the summer growing period.…”
Section: Collection Sitesmentioning
confidence: 99%
“…In tropical closedcanopy forests most leaf biomass occurs in the upper canopy. Well-lit leaves have higher photosynthetic rates and have shorter life spans compared to more shaded leaves, although this is not always observed (Parker et al, 1989;Wright and Cannon, 2001;Santiago and Wright, 2007). Reich et al (1991) found, on a global scale, an inverse logarithmic relationship between leaf life span and net photosynthetic rate.…”
Section: Introductionmentioning
confidence: 98%
“…The current landscape of SERC is a patchwork of several stages of old field succession and other land cover such as grass and buildings. Forests at SERC have been classified into the Tulip poplar association [6,7,18]. The most common tree species include tulip poplar (Liriodendron tulipifera), sweetgum (Liquidambar styraciflua), red maple (Acer rubrum), several oaks (Quercus spp.…”
Section: Study Sitementioning
confidence: 99%
“…With few exceptions, however (Kunkel-Westphal and Kunkel 1979;Turnbull and Madden 1983;Carpenter and Horowitz 1988), these studies are concerned primarily with total litter mass and nutrient cycling and either they do not categorize foliage mass by species (Klinge and Rodrigues 1968;Bongers et al 1988;Dantas and Phillipson 1989) or they do not provide detailed information on the position of trees in the source forest (Coulter and Allaway 1979;Kunkel-Westphal and Kunkel 1979;Mayack et al 1989). A recent study by Parker et al (1989) is one of the first to investigate littersource forest relationships on a per-species basis, although the motivation was not for paleoecological analysis.…”
mentioning
confidence: 99%